Experimental Development Of Future Physics Teacher Competence (Eurasian Journal of Learning and Academic Teaching, 2025)
This article examines new pedagogical approaches to training future physics teachers. The authors address the connections between theory and practice, as well as the development of experimental competence and the application of innovative technologies in physics teaching